Pengaruh Perilaku Keuangan Dan Pengetahuan Keuangan Terhadap Transaksi Pembayaran Non Tunai Pelaku UMKM di Daerah Perbatasan Kecamatan Raihat Kabupaten Belu - Januaria Kartika Ati; Maria Indriyani Hewe Tiwu; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the influence of financial behavior on non-cash payment behavior and to determine the influence of financial knowledge on non-cash payment transactions in the community of Raihat District. This study uses primary data by distributing questionnaires to 30 respondents in Raihat District who are MSME actors. This study uses purposive sampling. The data analysis in this study uses multiple linear regression analysis with the results of the study showing that financial behavior and financial knowledge have a significant effect on non-cash payment transactions in the community in Raihat District.